2009
DOI: 10.1007/s00040-009-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Division of labour and social insect colony performance in relation to task and mating number under two alternative response threshold models

Abstract: Some social insects exhibit an exceptionally high degree of polyandry. Alternative hypotheses exist to explain the benefits of multiple mating through enhanced colony performance. This study critically extends theoretical analyses of the hypothesis that enhanced division of labour confers fitness benefits to the queen that are sufficient to explain the observed mating frequencies of social insects. The effects of widely varying numbers of tasks and matings were systematically investigated in two alternative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…Our results on the strong effect of multiple mating on intra- and inter-colonial genotypic variance conforms well with previous theoretical work [51], computer simulations of colony task performance [9], and empirical studies showing benefits of multiple mating for behavioral organization [14], disease resistance [17], and colony performance [16]. In concordance with previous studies the main benefit of multiple mating for genetic diversity is gained when mating numbers are low and the increase in variance becomes marginal for mating number above 20, irrespective of the number of contributing loci or other modifications of the genetic architecture.…”
Section: Discussionsupporting
confidence: 91%
“…Our results on the strong effect of multiple mating on intra- and inter-colonial genotypic variance conforms well with previous theoretical work [51], computer simulations of colony task performance [9], and empirical studies showing benefits of multiple mating for behavioral organization [14], disease resistance [17], and colony performance [16]. In concordance with previous studies the main benefit of multiple mating for genetic diversity is gained when mating numbers are low and the increase in variance becomes marginal for mating number above 20, irrespective of the number of contributing loci or other modifications of the genetic architecture.…”
Section: Discussionsupporting
confidence: 91%
“…Theoretical work has investigated the role of interindividual variability and genetic architecture on colony performance (e.g. Page & Mitchell, ; Bertram, Gorelick & Fewell, ; Myerscough & Oldroyd, ; Jeanson et al , ; Gove et al , ; Tarapore, Floreano & Keller, ). Despite variations in model structures, these studies generally showed that interindividual variability is beneficial to colonies.…”
Section: Ultimate Consequences: How Does Variability Affect the Colony?mentioning
confidence: 99%
“…These benefits could arise because there is a genetic basis to worker castes (e.g. Hughes et al , 2003; Hughes & Boomsma, 2007; Jaffe et al , 2007) such that colonies founded by polygamous queens are more efficient in their division of labour (review: Smith et al , 2008; theoretical models: Gove et al , 2009; Tarapore, Floreano & Keller, 2010). There is also good evidence that patrilines differ in their susceptibility to certain diseases, so that a more genetically diverse colony workforce reduces the spread of disease and/or parasites, and lowers the mean level of worker mortality (e.g.…”
Section: Introductionmentioning
confidence: 99%